The recent progress and future of oxygen reduction reaction catalysis: A review. (March 2017) - Stacy, John; Regmi, Yagya N.; Leonard, Brian; Fan, Maohong
Abstract: Proton Exchange Membrane Fuel Cell (PEMFC) technology is an exciting alternative energy prospect, especially in the field of transportation. PEMFCs are three times as efficient as internal combustion (IC) engines and emit only water as a byproduct. The latter point is especially important in a day and age when climate change is upon us. However, platinum required to catalyze the sluggish oxygen reduction reaction (ORR) which takes place on the cathode of the PEMFC has rendered fuel cell automobiles economically unviable until now. Therefore, the pursuit of an inexpensive replacement for platinum has become an active research area. This review covers the promising progress made in this field since 2011. Some of the more promising catalysts reviewed include alloys such as Pt/Pd nanotubes which outperform their platinum counterpart by nine fold and a Pt/Ni alloy which improves upon Pt activity by 16 times. Platinum-free catalysts such as iron carbide and modified graphene which rival Pt activity are also reviewed.